La reacción cristiana ante el "Kατὰ Kριστιανῶν" de Porfirio de Tiro - Rodríguez Moreno, Inmaculada (2016)
The neoplatonist Porphyrius of Tyrus caused controversy among Christians with his Contra Christianos, so that they did not take a long time in reacting from various fields. This teatrise was a great novelty in relation to other previous works, because, in this case, the criticism was directed to the two main pillars of Christianity: the Scriptures and Christ. This paper analyses the repercussion of Contra Christianos by Porphyrius and those christian apologists who answered directly to it.
Keywords: Porfirio; Cristianismo